Broken: women's stories of intimate and institutional harm and repair - Young Larance, Lisa (Gender and justice, 2024)
"In the U.S., the second-wave feminist fight to achieve legal and societal recognition of men's violence against women leaned heavily on the victim-offender binary, which has since become inscribed in funding schemes, legal remedies, and intervention approaches. In Broken, scholar-practitioner Lisa Young Larance interviews women who participated in antiviolence intervention and draws on her own extensive practice in the field to explain how this binary erases the trauma histories of those who both survive and cause harm. Calling for a more holistic conception of interpersonal violence that makes room for human complexity, Broken illuminates the connections across race, class, and sexual orientation that facilitate women's healing and repair"--